Animal and plant proteins as alternative ingredients in diets for sub‐adult olive flounder Paralichthys olivaceus at farm conditions. (15th February 2022) - Choi, Wonsuk; Hamidoghli, Ali; Rivero, Cynthia Jo; Bae, Jinho; Lee, Seunghyung; Lee, Bong‐Joo; Hur, Sang‐Woo; Han, Hyonsob; Choi, Youn Hee; Bai, Sungchul C.
Abstract: A 20‐week feeding trial was performed to evaluate the optimum level of animal and plant protein sources as substitutes of fishmeal (FM) in the diets of sub‐adult olive flounder ( Paralichthys olivaceus) under farmed conditions. Groups of ninety fish averaging 478 ± 4.7 g (mean ± SD) were randomly distributed into four treatments in triplicates. An FM‐based diet was used as control (CON) and three other diets replaced 20% (APP20 ), 30% (APP30 ) and 40% (APP40 ) of FM with animal (tankage meal and poultry by‐product meal) and plant (soy protein concentrate) protein sources. Weight gain, specific growth rate and protein efficiency ratio were not significantly different among fish fed all the experimental diets ( p  > 0.05). The feed efficiency of fish fed the APP40 diet was significantly lower than those of fish fed the other experimental diets ( p  < 0.05). Non‐specific immune responses such as superoxide dismutase activity and lysozyme activity of fish fed all the experimental diets were not significantly different ( p  > 0.05). Intestinal villi length of fish fed the CON diet was significantly higher than those of fish fed the other diets ( p  < 0.05). Based on the results of growth performances and the non‐specific immune responses, the dietary combination of animal and plant protein sources could replace up to 40% of FM in sub‐adult olive flounder.